Analisis Faktor-Faktor yang Mempengaruhi Produksi Petani Kopi Robusta Kecamatan Pupuan Kabupaten Tabanan - Ni Putu Arvina Frilian Maharani; Made Kembar Sri Budhi (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Pupuan Subdistrict is one of the largest producers of Robusta coffee in Tabanan Regency, which undoubtedly holds great potential for the development of smallholder coffee plantations. However, in the production process, farmers still face various obstacles, such as suboptimal land management, labor shortages during the harvest season, and uneven and limited adoption of technology. This research aims to determine the effects of land area, labor, and technology on coffee production in Pupuan Subdistrict, Tabanan Regency, both simultaneously and partially. This study employed an quantitative method using primary data obtained through the distribution of questionnaires and in-depth interviews with Robusta coffee farmers in Pupuan Subdistrict, Tabanan Regency. The number of respondents in this study was 97 people from four different villages, namely Belimbing Village, Sanda Village, Batungsel Village, and Pujungan Village. The independent variables used included land area, labor, and technology, while the dependent variable was robusta coffee production, with data analysis performed using multiple linear regression. The results of the study show that land area, labor, and technology collectively have a significant effect on Robusta coffee production. Individually, each of these variables, land area, labor, and technology also has a positive and significant effect on Robusta coffee production in Pupuan Subdistrict, Tabanan Regency.